(3eHGOF GdEbJUGO GdfbOj hGdeUQaj (B:s (3EVGAGJ Mhd GdLgGR GdeUQaj hGdSjGSGJ GdfbOjI aj JMGdjd fXQjI hebGQHGJ cejI (B/s - (3Ndjd, YHO GdbGOQs ((3GdLRGFQ(B: s (3OjhGf GdeWHhYGJ GdLGeYjI(B, s, 2014)
(3JfGhd gPG GdcJGH eHGOF GdGbJUGO GdfbOj hGdeUQaj, MjK JfGhd ef NdGd aUhdg EVGAGJ Mhd GdLgGR GdeGdj hGdeUQaj , hGdNRjfI GdYehejI hGdHfc GdeQcRj , HGdEVGaI Gdi GdeDSSGJ GdeUQajI hGdeGdjI GdCNQi (B"(3Hfhc JLGQjI, Hfhc GSJKeGQ, Hfhc eJNUUI (B" (3hGdSjGSGJ GdfbOjI hGdeGdjI, hGNJJe GdcJGH ef NdGd JMdjd fXQj hcej daYGdjI GdSjGSI GdfbOjI hGdeGdjI, HGSJNOGe fehPL (BIS_LMs
(3GdeQGLY U(B.277s
Keywords: (3GdEbJUGO GdfbOjs